Ant assemblage and its ecological functions in coffee crop systems - Angotti, Marina Acero (2018)
The agricultural land expansion has become one of the main causes for biodiversity loss, and this loss can be even greater depending on the type of crop management. Thus, the aim of this thesis was to assess the influence of different coffee crop managements on the assemblage and ecological functions of ants, as well as to evaluate the influence of landscape and local variables on these animals. The sampling was taken in coffee monocultures and surrounding forest fragments at the counties of Machado and Poço Fundo, Minas Gerais, Brazil. In the first chapter, I used pitfall traps to collect the ant assemblage at different coffee crops under conventional and organic managements. Then, I evaluated the influence of the management on the ant assemblage, as well as the local environmental variables. I found that the use of pesticide in the conventional crops might be one of the factors responsible for the changes on the ant assemblage, and that canopy openness explained the variation on the ant assemblage composition. In the second chapter, I evaluated the removal of artificial seeds and insect predation by ants in forest áreas and two coffee management (conventional and organic). I found that the coffee crop, independently of its management, was responsible for the composition of predator species, and that canopy openness was related with the changing of predator species composition. At last, in the third chapter I compared the influence of variables at landscape and local scales on the ant assemblage in forest fragments and coffee crops. I found that the ants responded to both landscape and local variables, and that the ant assemblage composition in the forest was related to the percentage of coffee crop. Percentage of coffee crop was the most important variable to explain ant composition in the forest, followed by canopy openness. In the coffee monocultures, the ant composition was related only to the canopy openness. Therefore, the agricultural system is responsible for the change on the ant assemblage and we should consider management more natural practices strategies, such as organic managements, and inclusion of trees in the crops to decrease the canopy openness, which proportionate a favorable environment to the ant assemblage. Moreover, ants are good organisms to be used as models for assessments of environmental impacts that are related to the assemblage and ecological functions. Besides, ants can respond to variables at both landscape and local scales.